Development of a Digital-Based 360-Degree Performance Appraisal System to Enhance the Objectivity of Employee Evaluation - Abdul Tahir; Jasman Jasman (STEKOM PRESS, 2026)
Employee performance appraisal is a strategic instrument in human resource management that directly influences competency development, job promotion, and remuneration policies. However, conventional top-down appraisal systems are often confronted with issues of subjectivity, evaluator bias, and limited transparency in the evaluation process. This study aims to develop a digital-based 360-degree performance appraisal system that integrates multi-source perspectives, including supervisors, peers, subordinates, and self-assessment, within a unified platform. The study employed an Agile-based system development method using an iterative approach, supported by data collection techniques consisting of literature review, business process observation, and in-depth interviews with stakeholders within higher education institutions. The system was designed using a web-based architecture with role-separated modules, a role-based access control (RBAC) authentication mechanism, and score normalization algorithms to ensure assessment consistency. The testing results indicate that the system successfully improves evaluation objectivity through standardized weighting distribution, enhances transparency through audit trail and real-time reporting features, and accelerates the recapitulation process by up to 78% compared to manual methods. Furthermore, the system effectively reduces single-evaluator bias and strengthens accountability in human resource management decision-making. This study concludes that the digitalization of 360-degree performance appraisal functions not merely as an automation tool, but as a strategic instrument for establishing a fair, transparent, and data-driven evaluation culture.